British Admiralty Small Scale Charts, Ancient and Modern - Harper, Brian (The International Hydrographic Review, 2018)
This paper is a personal review of the very small scale charts produced by the British Admiralty. It includes a valediction to the UK Hydrographic Office’s series of world small scale fathoms charts dating from the 19th century, and goes on to describe the planning and construction of the first modernised metric chart in the replacement series. Also included is a description of the differences between the old and new charts, and a detailed account of the technological processes used to produce the new series.